Paraguay : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This Selected Issues paper analyzes the background, stages and developments, and estimation of the direct costs of Paraguay's banking crisis. The paper provides the estimates on the size and evolution of the informal sector, and examines the extent to which the national accounts capture informal activity. The study also estimates the potential output and total factor productivity by examining trends in output, investment, and population growth as well as the direction and size of fiscal impulse on its economy. The paper also provides a statistical appendix report of Paraguay.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet